2012
DOI: 10.1080/10509674.2012.683323
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Future: Incarcerated Women's Views of Reentry Success

Abstract: Research reveals that most incarcerated adults are optimistic about their chances of success after release and believe they will be less likely to reoffend than other prisoners. Moreover, studies suggest that optimism shapes desistance. This raises the interesting question of how and why female inmates maintain an optimistic outlook about their postrelease. The current study uses in-depth interviews with 26 incarcerated women to assess inductively their perceptions of life after prison and the self-enhancing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 29 publications
3
34
0
6
Order By: Relevance
“…Research based on self-report measures indicates that mother and child stress can surge during reunifi cation (Cobbina & Bender, 2012 ), and mothers' cortisol values at T3, the highest recorded during this study, provide additional support for this phenomenon, especially as hair cortisol levels were compared to participants' own baseline levels obtained during imprisonment. Surprisingly, at T3, maternal cortisol levels did not relate to mother-child contact in the form of living together, frequency of contact, and duration since last contact with their child.…”
Section: Maternal Stress and Adjustmentsupporting
confidence: 54%
“…Research based on self-report measures indicates that mother and child stress can surge during reunifi cation (Cobbina & Bender, 2012 ), and mothers' cortisol values at T3, the highest recorded during this study, provide additional support for this phenomenon, especially as hair cortisol levels were compared to participants' own baseline levels obtained during imprisonment. Surprisingly, at T3, maternal cortisol levels did not relate to mother-child contact in the form of living together, frequency of contact, and duration since last contact with their child.…”
Section: Maternal Stress and Adjustmentsupporting
confidence: 54%
“…They described their euphoria on leaving prison, and for some men on release this was followed by a rapid plunge into despair and suicidal thoughts. This is consistent with several studies that found that prisoners frequently have high expectations about their pending life in the community and then experience frustration, disappointment, fear and anxiety on release (Binswanger et al, 2011;Cobbina & Bender, 2012;Howerton et al, 2009;Shinkfield & Graffam, 2010). The emotional response to cycling in and out of prison can be further understood by reference to Giddens (1984, p. 61), who proposed that when accustomed routines are suddenly disrupted with a "critical situation" -for example, leaving the structured environment of prison -responses can include "rapid emotional oscillation between depression and elation" and "a concentration on immediate events and loss of any long term perspectives", related to the impact of anxiety and fear.…”
Section: The Ambivalent Agentsupporting
confidence: 91%
“…Assuming a recidivism rate where half of the people released from prison will return to prison within 5 years, the responses present within these two samples suggest that these currently incarcerated men and women have overly optimistic perceptions about their future. Cobbina and Bender (2012) interviewed 26 women who had returned to prison within 3 years of release about their perceptions of success. The interviewees commonly described their own perceptions of success upon reentry against their perceptions of the success of other women experiencing incarceration, highlighting the regularity of self-enhancement bias.…”
Section: Perceptions Of Reentry Successmentioning
confidence: 99%
“…In this study, we explore the role that perceived uncertainty of success plays in shaping women's expectations about life after prison. Building upon work by Cobbina and Bender (2012), Visher and O'Connell (2012), and Friestad and Hansen (2010), we explore 1) the demographic characteristics that are associated with perceived uncertainty for reentry success and 2) the extent to which this perceived uncertainty is associated with the women's identification of specific obstacles upon their release. Our data represent standardized, semi-structured interviews of 200 women incarcerated in minimum and medium-security prisons in the women's prison complex in Arizona.…”
mentioning
confidence: 99%